Stauroceras chaitosiphon (Homoptera, Aphidinea) - новый для фауны Украины вид тли - Журавлев, В.В. (Інститут зоології ім. І.І. Шмальгаузена НАН України, 2001)
Впервые описаны летняя бескрылая и крылатая партеногенетические самки нового для фауны Украины вида тлей Stauroceras chaitosiphon Bцrner, найденные в Дунайском биосферном заповеднике. Рассмотрен вопрос о самостоятельности рода Stauroceras Borner. The summer apterous viviparous and alate viviparous females of Stauroceras chaitosiphon Borner are described. The species is recorded for the first time in the Ukraine. The problem of validity of the genus
Stauroceras Borner is discussed.